(3TQM GdCSeGA GdMSfis - (3YHO GdSdGe Hf YHO GdQMef Hf eMeO GddNej GdETHjdj, CHh GdMce,J (B536 (3g` s ((3eMeO Hf eMeO Hf eMeO Hf CHj HcQ GdYjGTi s)
(3ChdgG (B:s
(3GSeg GdTgjO SHMGfg hdg GdMeO s
(3BNQgG (B:s
(3eG jbQDg HdSGfg hjTGgO HYbdg s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1031s
Keywords: (3GdLZQGajG h GdHdOGfs